The role of the use of visualization tools for teaching sorting algorithms in online teaching - Mladenović, Monika; Udiljak, Lucija; Boljat, Ivica (Polytechnica, 2021)
Learning and teaching of sorting algorithms are very challenging for students and teachers as well. The issues are more highlighted in the online form of teaching which was the only form of schooling from March to June of the school year 2019/2020 in Croatia due to the COVID-19 pandemic. The use of visualization tools could be used for lowering the abstraction of complex programming concepts such as sorting algorithms. We conducted research among two high-school classes (n=52) in one science and mathematics high school while teaching sorting algorithms during online schooling. In the experimental group, we used visualization tools VisuAlgo and Python Tutor for teaching sorting algorithms and their implementation in Python as well. We examined students’ attitudes towards programming and online teaching as well. We present the results of the research in this paper.